GENDER CONSTRUCTION AND THE VALUES OF DEEP FEMINISM SCHEHERAZADE GOES WEST FATIMA MERNISSI - Ayu Ratna Hidayati; Muhammad Alfikri (KABILAH : Journal of Social Community, 2022)
Abstract: By focusing on the story of a late 20th-century Arab woman who wrote about her journey to the west. Fatima Mernissi, in Scheherazade Goes West: Different Cultures, Different Harems (Mernissi, 2001), with her intellectual journey seeks and concludes answers to her questions about the gender code of European-American philosophy and popular culture by deconstructing not only Western male orientalist fantasies about Muslim women but also the “harem of Western women” of hypervisibility and body shaming. She goes a step further by exploring and dismantling patriarchal norms by crossing this apparent “East-West” difference through modes of critique of secular and Islamic feminists. She produces, and distributes texts, to advance the "double criticism" of local and colonial patriarchy into a continuous analysis in her travel notes. This article stipulates that the author analyzes the contents of the literary works studied with the critical discourse analysis approach model by becoming a facilitating framework, and in the end, the methodology comes from ways of knowing based on social construct and cultural values that are the author's study. Keywords: Fatima Mernissi, Gender, Feminism, Islam, Western